Mechanically Matched Silicone Brain Implants Reduce Brain Foreign Body Response. Issue 3 (27th January 2021) - Zhang, Edward N.; Clément, Jean‐Pierre; Alameri, Alia; Ng, Andy; Kennedy, Timothy E.; Juncker, David
Abstract: Brain implants are increasingly used to treat neurological disorders and diseases. However, the brain foreign body response (FBR) elicited by implants affects neuroelectrical transduction and long‐term reliability limiting their clinical adoption. The mismatch in Young's modulus between silicon implants (≈180 GPa) and brain tissue (≈1–30 kPa) exacerbates the FBR, resulting in the development of flexible implants from polymers such as polyimide (≈1.5–2.5 GPa). However, a stiffness mismatch of at least two orders of magnitude remains. The study introduces 1) the first mechanically matched brain implant (MMBI) made from silicone (≈20 kPa); 2) new microfabrication methods; and 3) a novel dissolvable sugar shuttle to reliably implant MMBIs. MMBIs are fabricated via vacuum‐assisted molding using sacrificial sugar molds and are then encased in sugar shuttles that dissolved within 2 min after insertion into rat brains. Sections of rat neocortex implanted with MMBIs, polydimethylsiloxane (PDMS) implants, and silicon implants are analyzed by immunohistochemistry 3 and 9 weeks post‐implantation. MMBIs result in significantly higher neuronal density and lower FBR within 50 µm of the tissue‐implant interface compared to PDMS and silicon implants, suggesting that materials mechanically matched to brain further minimize the FBR and can contribute to better implant functionality and long‐term reliability. Abstract : Sacrificial sugar molds coupled with vacuum‐assisted molding (VAM) enable the creation of the first mechanically matched brain implants (MMBI) made from silicone (≈20 kPa). The MMBIs are encased in a sugar shuttle using VAM and implanted into rat brains. MMBIs elicit a reduced brain foreign body response compared to polydimethylsiloxane and silicon implants indicating superior tissue compatibility.